Phenethylamine Does Not Accelerate Healing in Staphylococcus aureus-infected Wounds in Mice - Mufina, Hana Dian; Hidayati, Dewi; Zulaika, Enny; Luqman, Arif (Biomedical Sciences and Clinical Medicine, 2025)
Objective Bacterial infections can lead to a delay in the wound healing process. Recent studies have reported that trace amines accelerate wound healing by enhancing keratinocyte migration thus promoting a faster wound re-epithelization process. This study aimed to investigate the effects of phenethylamine on Staphylococcus aureus-infected wounds by using a mouse model. Methods This study used mice as a model for in vivo skin wound experi-ments. S. aureus was applied on skin wounds on the backs of the mice. Phenethylamine in different concentrations was also applied either once daily or every two days. The wound diameter, abscess formation, and swollen area were observed every two days for 14 days. Results Different concentrations and frequencies of phenethylamine applications on the wound exhibited no significant wound healing acceleration. Phenethylamine applications also did not show significant effects on abscess formation or swelling. Conclusions S. aureus infection may overwhelm the wound healing acceleration effects of phenethylamine resulting in no significant improvement in healing.